2020
DOI: 10.1002/est2.212
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic salt hydrate for thermal energy storage application: A review

Abstract: Salt hydrates are one of the most common inorganic compounds that are used as phase change material (PCM). These are available for a wide range of phase transition temperature for thermal energy storage (TES) application. They have some most desired properties for TES applications like high latent heat value, good thermal conductivity, nonexpensive, and were nonflammable. Besides these, due to the undesirable properties like phase segregation, supercooling, and corrosion to the containers, this PCM not recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 120 publications
(198 reference statements)
0
22
0
Order By: Relevance
“…Changes in CO 2 surroundings along the studied pressure–temperature paths must be considered while interpreting the results of the present study, where the molecule is first dissolved in the aqueous solutions, then “enclathrated” upon cooling, and finally released by heating. The addition of salts, methanol, or ammonia to water-rich phases decreased both specific heat capacity and enthalpy. These values for these compounds in the solid state, forming salt hydrates, are usually within the ranges of 1–2 J g –1 K –1 and 100–300 J g –1 . , …”
Section: Introductionmentioning
confidence: 99%
“…Changes in CO 2 surroundings along the studied pressure–temperature paths must be considered while interpreting the results of the present study, where the molecule is first dissolved in the aqueous solutions, then “enclathrated” upon cooling, and finally released by heating. The addition of salts, methanol, or ammonia to water-rich phases decreased both specific heat capacity and enthalpy. These values for these compounds in the solid state, forming salt hydrates, are usually within the ranges of 1–2 J g –1 K –1 and 100–300 J g –1 . , …”
Section: Introductionmentioning
confidence: 99%
“…When all the samples had melted and reached the same temperature of 60 °C, they were suddenly exposed to a magnetic field and cool temperature environment inside the adiabatic bath, in conjunction with the temperature data recording until all the samples solidified. The experiment was repeated 20 times with a new sample for each measurement, which was used to evaluate each set of parameters due to the complex thermal properties of CoNHH and the possibility of the phase separation effect, which commonly occurs during the freezing-thawing cycle for salt hydrate PCMs [4][5][6][7]10 .…”
Section: T M ( O C)mentioning
confidence: 99%
“…Organic or inorganic PCMs, however, have their advantages and disadvantages 5 . In particular, a relatively high supercooling degree and phase separation effect are the main considerations for inorganic salt hydrate PCMs, besides the possibility of a change in the stoichiometric composition during heating and cooling 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, SSD suffers from supercooling and phase separation induced by incongruent melting, that reduce its enthalpy of fusion and limit its practical applications. , Different methodologies have been developed to solve these issues and form stable PCMs. For example, it has been demonstrated that the addition of nucleating agents can effectively decrease the supercooling degree. The most suitable nucleating agent for SSD is borax, which can reduce its supercooling from 15 to 1–2 °C. In addition, several approaches have been proposed to overcome phase separation, including adding thickening agents, , adding excess water, , and incorporating SSD within a porous medium. However, in many cases the reduction in phase segregation is occurred at the cost of a reduced thermal energy storage capacity of SSD, with a wide range of values reported in the literature (∼100–200 kJ/kg). , …”
Section: Introductionmentioning
confidence: 99%
“…18−20 However, in many cases the reduction in phase segregation is occurred at the cost of a reduced thermal energy storage capacity of SSD, with a wide range of values reported in the literature (∼100−200 kJ/ kg). 21,22 There is a growing interest in developing polymeric phase change composites, whereby the PCM can either be entrapped in the matrix or encapsulated into the polymer shell. 23 The use of polymers offers several benefits that are missing in the case of molecular modifiers.…”
Section: Introductionmentioning
confidence: 99%